2005
DOI: 10.1002/art.20858
|View full text |Cite
|
Sign up to set email alerts
|

Remission of proliferative lupus nephritis following B cell depletion therapy is preceded by down‐regulation of the T cell costimulatory molecule CD40 ligand: An open‐label trial

Abstract: Objective. Autoreactive B cells play a key role in tissue injury in systemic autoimmune disease, and therefore a treatment resulting in B cell depletion could have benefit. This open-label study was undertaken to evaluate the efficacy of the anti-CD20 monoclonal antibody rituximab in the treatment of lupus nephritis.Methods. Lupus patients with active proliferative nephritis (4 with focal disease and 6 with diffuse disease) received rituximab (4 weekly infusions of 375 mg/m 2 ) combined with oral prednisolone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
266
3
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(296 citation statements)
references
References 59 publications
16
266
3
11
Order By: Relevance
“…The data on B cell depletion obtained in the present study show that patients who had the shortest duration of B cell depletion (2 months) showed a trend toward a less favorable histopathologic outcome (WHO classes V and IV/V) compared with patients who had more longstanding B cell depletion times. Since only 7 patients were studied, it is not possible to draw any firm conclusions from this finding, but similar observations of short B cell depletion times and unresponsiveness to treatment have been described by others (23). Interestingly, a correlation between short B cell depletion times and high numbers of circulating B cells before treatment has also been shown in a larger patient population (44).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The data on B cell depletion obtained in the present study show that patients who had the shortest duration of B cell depletion (2 months) showed a trend toward a less favorable histopathologic outcome (WHO classes V and IV/V) compared with patients who had more longstanding B cell depletion times. Since only 7 patients were studied, it is not possible to draw any firm conclusions from this finding, but similar observations of short B cell depletion times and unresponsiveness to treatment have been described by others (23). Interestingly, a correlation between short B cell depletion times and high numbers of circulating B cells before treatment has also been shown in a larger patient population (44).…”
Section: Discussionmentioning
confidence: 49%
“…In addition, a simultaneous reduction or disappearance of CD3ϩ and CD4ϩ lymphocyte subpopulations was noted in a majority of the patients. Interestingly, Sfikakis et al (23) recently reported a reduction in T cell subsets as well as T helper cell activation after rituximab treatment, thus demonstrating that B cell depletion not only affects B cell populations but may have other regulatory effects on mediators of inflammation and functions of the immune system. Serum levels of immunoglobulins are generally maintained after rituximab therapy, which further suggests that B lymphocytes in the central lymphoid organs are not eliminated completely and that long-lived plasma cells may maintain antibody production in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ethnic factors, the 2 RCTs included American patients, predominantly from the US and Canada, but also from Mexico, Brazil, and Argentina. However, the majority of patients from recent uncontrolled studies were European (1,6,7,9,11,12). This ethnicity is important because some studies have suggested a variable therapeutic response to the main immunosuppressive agents in different ethnic groups (13).…”
Section: To the Editorsmentioning
confidence: 99%
“…There is increasing evidence that B cells promote autoimmune disease not only by the production of auto-antibodies but also by serving as APCs for autoreactive T cells and by secretion of cytokines. Accordingly, remission of lupus nephritis after B cell depletion was associated with a decrease in T cell activation in blood (1). Most healthy individuals possess significant numbers of auto-reactive B cells (2) suggesting that additional events promoting alterations in B cell tolerance are required for initiation of autoimmune symptoms.…”
Section: Introductionmentioning
confidence: 99%